Etiological profile and treatment outcome of epistaxis at a tertiary care hospital in Northwestern Tanzania: a prospective review of 104 cases - Gilyoma, Japhet M (BioMed Central, 2011)
BACKGROUND: Epistaxis is the commonest otolaryngological emergency affecting up to 60% of the population in their lifetime, with 6% requiring medical attention. There is paucity of published data regarding the management of epistaxis in Tanzania, especially the study area. This study was conducted to describe the etiological profile and treatment outcome of epistaxis at Bugando Medical Centre, a tertiary care hospital in Northwestern Tanzania. METHODS: This was a prospective descriptive study of the cases of epistaxis managed at Bugando Medical Centre from January 2008 to December 2010. Data collected were analyzed using SPSS computer software version 15. RESULTS: A total of 104 patients with epistaxis were studied. Males were affected twice more than the females (2.7:1). Their mean age was 32.24 ± 12.54 years (range 4 to 82 years). The modal age group was 31-40 years. The commonest cause of epistaxis was trauma (30.8%) followed by idiopathic (26.9%) and hypertension (17.3%). Anterior nasal bleeding was noted in majority of the patients (88.7%). Non surgical measures such as observation alone (40.4%) and anterior nasal packing (38.5%) were the main intervention methods in 98.1% of cases. Surgical measures mainly intranasal tumor resection was carried out in 1.9% of cases. Arterial ligation and endovascular embolization were not performed. Complication rate was 3.8%. The overall mean of hospital stay was 7.2 ± 1.6 days (range 1 to 24 days). Five patients died giving a mortality rate of 4.8%. CONCLUSION: Trauma resulting from road traffic crush (RTC) remains the most common etiological factor for epistaxis in our setting. Most cases were successfully managed with conservative (non-surgical) treatment alone and surgical intervention with its potential complications may not be necessary in most cases and should be the last resort. Reducing the incidence of trauma from RTC will reduce the incidence of emergency epistaxis in our centre.